A relational model for assessing internal communications and organizational bonds: the importance of affective relations and the role of the immediate supervisor - Videira, Denise Pragana (Revista de Administração da UFSM, 2023)
Purpose – To analyze the factors related to the internal communication process that influence the organizational bonds (commitment, entrenchment, and consent) between workers and their employing organizations. Design/methodology/approach – Qualitative and quantitative research instruments were employed in a sample field consisting of four large organizations in Brazil. Findings emerged from Content Analysis, Exploratory Factor Analysis (EFA) and Structural Equation Modelling (SEM).The qualitative phase involved the participation of 23 respondents. The quantitative phase sample comprised 401 respondents. A scale was developed to assess workers' perceptions of communication processes. Findings – A relationship between communication processes and organizational bonds was confirmed. Immediate leader communication proved to be a highly significant factor in the internal communication process, as well as affective communication, which directly impacts commitment and acts on engaging communication, which in turn influences commitment. It was observed that the consent bond, through the subordination, directly impacts commitment, albeit in a negative manner. Originality/value – The study contributes to the field of organizational communication by introducing the IOCS (Internal Organizational Communication Scale) and paves the way to further the still nascent debate on the forms of interaction between organizations and their employees resulting from new management models, labor contracts, as well as organizational value and purposes, stemming from the changes brought about by the Covid-19 heath crisis.